1984
DOI: 10.1080/15287398409530573
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a cocarcinogen, ferric oxide, on the metabolism of benzo[a]pyrene in the isolated perfused lung

Abstract: An isolated perfused New Zealand rabbit lung preparation was used to investigate the effects of a cocarcinogen, ferric oxide (Fe2O3), on the metabolism of benzo[a]pyrene (BaP), a ubiquitous potent carcinogen that has been associated with the increased incidence of human bronchiogenic carcinoma in occupational and urban settings. [14C]-BaP was administered intratracheally to an isolated perfused lung (IPL) preparation with and without Fe2O3 after intraperitoneal pretreatment of the whole animal with BaP or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…carcinogenesis [55]. Previous study indicated that high exposure is associated with an increased levels of aromatic adducts in PAHs exposed population [56] and suggested that alterations of PAH metabolism may play a crucial role in long-term particle-associated lung diseases and injuries induced by free radicals (FR), which are generated during its metabolism [57]. Oxidative stress and disturbed antioxidant status are well established in previously published studies of many childhood diseases [58,59].…”
Section: Variablesmentioning
confidence: 98%
“…carcinogenesis [55]. Previous study indicated that high exposure is associated with an increased levels of aromatic adducts in PAHs exposed population [56] and suggested that alterations of PAH metabolism may play a crucial role in long-term particle-associated lung diseases and injuries induced by free radicals (FR), which are generated during its metabolism [57]. Oxidative stress and disturbed antioxidant status are well established in previously published studies of many childhood diseases [58,59].…”
Section: Variablesmentioning
confidence: 98%
“…We also showed that in vivo short-term exposure to BaP coated onto Fe 2 O 3 particles induced more pronounced proteinase/antiproteinase imbalance, oxidative stress conditions, inflammatory response and apoptosis than exposure to BaP alone (Garçon et al, 2000(Garçon et al, , 2001aGosset et al, 2003). Other authors have suggested that alteration of the metabolic activation of BaP may play a key role in long-term particle-associated lung disease (Warshawsky et al, 1984;Greife & Warshawsky, 1993;Cheu et al, 1997). Any influence of iron in PAH/iron oxide mixtures on the capacity of PAHs to induce metabolizing enzymes will be one of many ways in which iron oxides can affect PAH carcinogenicity (Vakharia et al, 2001a, b).…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, Warshawsky et al (1984) attempted to stimulate the metabolic activation of BaP in lungs using an isolated perfused lung model in the presence of Fe 2 O 3 under different exposure conditions. They showed that exposure to Fe 2 O 3 in the presence of BaP led to increased production of adverse metabolites.…”
Section: Discussionmentioning
confidence: 99%